Hiob in Qumran : Der Beitrag der Hiobhandschriften aus Qumran zur Text- und Literargeschichte des Hiobbuchs - Luther, Rebekka, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
The six manuscripts from Ḥirbet Qumran (2Q15, 4Q99, 4Q100, 4Q101, 4Q157, 11Q10) are the oldest textual witnesses of the Hebrew Book of Job, which received its final redaction during the 3rd century BCE. But their different characteristics and fragmentary condition make it hard to draw a picture on what these textual witnesses actually testify to. This study combines Text - and Literarkritik while considering their individual features. The results unveil a history of reception of the image of Job, which goes hand in hand with an ongoing production and reworking of the text. In dieser Studie werden die sechs fragmentarischen Hiobmanuskripte aus Ḥirbet Qumran in text- und literarkritischen Einzelanalysen untersucht. Die Ergebnisse geben Einblick in die früheste Rezeptionsgeschichte und zeigen, welche Themen nach dem Abschluss der Großkomposition im 3. Jh. v. Chr. die weisheitliche Debatte um das Schicksal Hiobs prägten.